2018
DOI: 10.1007/s10096-018-3196-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for CTX-M gram-negative bacteria in hospitalized patients at a tertiary care hospital in Kilimanjaro, Tanzania

Abstract: Emergence and spread of extended spectrum beta-lactamase (ESBL)-producing gram-negative bacteria, mainly due to CTX-M, is a major global public health problem. Patients infected with ESBL-producing gram-negative bacteria have an increased risk of treatment failure and death. We investigated the prevalence and risk factors for CTX-M gram-negative bacteria isolated from clinical specimens of patients hospitalized at a tertiary care hospital in Kilimanjaro, Tanzania. Isolated gram-negative bacteria from inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
1
24
2
Order By: Relevance
“…While our study showed that of the factors investigated, only literacy levels (p value = 0.0058) and hospitalization (p value < 0.0001) actually affected the rate of CRE infections; the infection rates of enterobacteriaceae generally were found to be affected by factors such as age, marital status, level of education and hospital setting. Other studies proved that younger age group and hospitalization are common risk factors for Gram-negative enterobacteriaceae (GNE) infections [18,19] while hospitalization remains the leading cause of CRE infections [20][21][22]. Since hospitalization is a strong risk factor in CRE colonization; clinicians, other health workers and in fact, everyone should join hands to reduce patients' length of stay in hospitals as this will reduce the risk of spread of CRE as well as control them.…”
Section: Discussionmentioning
confidence: 99%
“…While our study showed that of the factors investigated, only literacy levels (p value = 0.0058) and hospitalization (p value < 0.0001) actually affected the rate of CRE infections; the infection rates of enterobacteriaceae generally were found to be affected by factors such as age, marital status, level of education and hospital setting. Other studies proved that younger age group and hospitalization are common risk factors for Gram-negative enterobacteriaceae (GNE) infections [18,19] while hospitalization remains the leading cause of CRE infections [20][21][22]. Since hospitalization is a strong risk factor in CRE colonization; clinicians, other health workers and in fact, everyone should join hands to reduce patients' length of stay in hospitals as this will reduce the risk of spread of CRE as well as control them.…”
Section: Discussionmentioning
confidence: 99%
“…Injudicious use of ceftriaxone may contribute to the high burden of AMR, including nosocomial infections with extended spectrum beta lactamase (ESBL)-producing Enterobacteriaceae, and complicate empirical treatment of severe bacterial infections. In view of the high prevalence of colonization and infections with ESBL positive Enterobacteriaceae in Tanzanian hospitals [15][16] [17] [18], increasing use of carbapenems in the future can be anticipated. In an attempt to limit empiric carbapenem use, the Tanzanian National Health Insurance Fund (NHIF) implemented a policy in July 2016 that limits carbapenem coverage to infections with a positive bacterial culture and sensitivity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Injudicious use of ceftriaxone may contribute to the high burden of AMR, including nosocomial infections with extended spectrum beta lactamase (ESBL)-producing Enterobacteriaceae, and complicate empirical treatment of severe bacterial infections. In view of the high prevalence of colonization and infections with ESBL positive Enterobacteriaceae in Tanzanian hospitals [21][22][23][24], increasing use of carbapenems in the future can be anticipated. In an attempt to limit empiric carbapenem use, the Tanzanian National Health Insurance Fund (NHIF) implemented a policy in July 2016 that limits carbapenem coverage to infections with a positive bacterial culture and sensitivity [25].…”
Section: Discussionmentioning
confidence: 99%